Investigation of oxidation process in self-terminating gate recess wet etching technique for AlGaN/GaN normally-off MOSFETs - Liu, Jingqian; Wang, Jinyan; Xu, Zhe; Jiang, Haisang; Yang, Zhenchuan; Wang, Maojun; Min Yu; Xie, Bing; Wu, Wengang; Ma, Xiaohua; Zhang, Jincheng; Hao, Yue (ELECTRONICS LETTERS, 2014)
A self-terminating gate recess wet etching technique with thermal oxidation of the AlGaN/GaN layer followed by etching in potassium hydroxide (KOH) solution was recently proposed by the present authors for normally-off AlGaN/GaN metal-oxide semiconductor field effect transistors (MOSFETs). In this present reported work, the oxidation process inside the AlGaN/GaN heterostructure involved in this technique was analysed using several material characterisation methods. The measurement results show that the concentration and depth of the O element distribution increase with increased thermal oxidation temperature. It is worth noting that after 650 degrees C oxidation almost no O element could be found in the GaN layer and the O element mainly locates in the AlGaN layer with an obvious correlation between the distribution of Al and O elements, where the Al(Ga)-oxide was detected by X-ray photoelectron spectroscopy, which could be etched by 70 degrees C KOH. Thus, self-terminating wet etching on the AlGaN/GaN material is achieved.